INTERPRETASI MAKNA CANTIK DI KALANGAN MAHASISWA DALAM PERSFEKTIF FENOMENOLOGI SOSIAL: Studi Pada Mahasiswa Tadris IPS IAIN Metro - Ulva, Siti Maria; Hamer, Wellfarina; Ayyuhda, Citra; Nurlatifah, Linda (Jurnal Studi Gender dan Anak, 2021)
Abstract : Beauty is the most beautiful gift that God gives to every woman, how to care for it is also a nature that cannot be separated from the discussion of women, especially in the current millennial era. Beauty for the perception of many women can be relative and difficult to describe, but its meaning can be seen in different perspectives. This study aims to reveal what the meaning of beauty looks like for students of the IAIN Metro Social Studies Department, because based on the author's observations it is found that there are differences in perceptions in terms of interpreting beauty which tend to be seen from appearance so that students try to look beautiful by wearing make-up on campus so that beauty becomes a necessity of social recognition, appreciation and self-actualization. This study was analyzed using the theory of Phenomenology by Alfred Schutz. This study uses a qualitative research method with a phenomenological study approach. The results showed that there were various perceptions of the meaning of beauty for each student, especially Tadris IPS IAIN Metro students in interpreting beauty which tended to be objective in terms of: (1) ideal body shape (2) white and bright skin (3) attractive (outer beauty) rather than subjective meaning as seen from (1) Intellectual Intelligence (2) Emotional Intelligence (3) Spiritual Intelligence (Inner Beauty). The meaning of beauty for students is very diverse, every effort is made to meet certain beauty standards because then they will be more confident, get praise and attention and feel welcomed in a social environment.